Methodology for risk assessment of multi-event scenarios on radioactive waste repository - Karyoung Choi; Minseok Kim; Kibeom Son; Gyunyoung Heo (Nuclear Engineering and Technology)
Deep geological disposal, which is a permanent method that isolates a storage facility in rocks 200 to 1000 m deep underground, plays a role in safely disposing spent nuclear fuel to prevent excessive radioactive species from leaking out and its safety should be primarily proved. Risk for various radionuclide leakage scenarios should be calculated to be used as a safety indicator. One of the scenarios that significantly affects the safety of repository is the occurrence of external events such as an earthquake scenario. Several occurrences of such external disasters are expected over a long period of time which the safety functions of the deep disposal site must be maintained. Rather than performing a conservative single event evaluation, we expected that performing a more realistic evaluation, such as considering the number of events, is preferrable for design and operation optimization, particularly in an early project phase. This paper suggests a need for assessing multi-event scenarios and the methodology for simulation of several external disasters using earthquakes as an example. The methodology and algorithm of simulating multiple earthquakes and assessing risk distribution under those events at repository site is introduced in GoldSim software, and its results are expected to be used at simulating other event scenarios.